Pola Guru dalam Pembentukan Akhlak dan Intelektual Siswa Program Pendidikan Khusus –Kulliatul Muallimin Wal Muallimat Al-Islamiyah Kediri Lombok Barat - Muhammad Zul Azhar; Muhammad Nursikin (Institut Agama Islam (IAI) Nurul Hakim, 2022)
The purpose of this study was to determine: 1) PAI teachers communication patterns on the moral formation of students; 2) PAI teachers communication patterns on the formation of students' intellectual 3) Factors Supporting and Inhibiting Communication Patterns of Islamic Religious Education Teachers on the Formation of Santri's Morals and Intellectual. This research is qualitative and is a field research using a case study approach. The subjects of this study were the supervisors of the Islamic Boarding School Kulliatul Muallimin wal Mulimalimat Al Islamiyah Kediri Special Education Program, the ustadz, students and guardians of students. Data collection techniques through observation, interviews, documentation and data triangulation. The results of the study indicate that the policies implemented by the pesantren in the formation of students' morals include; giving examples, fostering the character of students through the application of discipline, giving attention, giving advice, giving punishment, supervision. While the pattern of intelligence formation includes; question and answer, discussion, lecture, advice and reprimand. The supporting factors are: school facilities, cooperation with fellow teachers, a conducive environment.